HUBUNGAN PERILAKU PEROKOK DENGAN KEBERSIHAN GIGI DAN MULUT DI SMAN 1 MAJALAYA KABUPATEN BANDUNG (Poltekkes Kemenkes Bandung, 2023)
Introduction: Smoking is a global health problem because it can cause various diseases and even death. The prevalence of smoking in Indonesia is 28.8%, and in West Java the prevalence of smoking is in the first rank of 34 provinces which is 32.0%, and the prevalence of smoking at the age of >15 years in 2018 is at a high rate (62.9 %). A number of studies show that smokers start smoking at the age of 11 and 13 years and 85-90% start smoking before the age of 18 years, and high school students with peers who smoke are 5 times more likely to smoke than non-smokers. have friends who smoke. In addition, there are several factors that cause students to smoke, including students having the motivation to smoke cigarettes because they want to try it after suggestions appear to try smoking from within themselves after seeing people around them smoking. Smoking not only has a systemic effect, but can also cause pathological conditions in the oral cavity. Teeth and soft tissues of the oral cavity are parts that can be damaged by smoking. Methods: This research is a non-experimental quantitative research and uses the type of analytical research. Data were collected by distributing questionnaires containing questions about smoking behavior and followed by examination of the Hygiene Index on 40 student respondents of SMAN 1 Majalaya, Bandung Regency according to the criteria. The statistical test carried out is the Chi-Square test. Results: The behavior of smokers and the dental and oral hygiene of the respondents were in the moderate category. And obtained the relationship between smoking behavior with dental and oral hygiene (p = 0.011 <0.05). Conclusion: There is a significant relationship between smoking behavior and oral hygiene at SMAN 1 Majalaya, Bandung Regency.